PANDANGAN HUKUM ISLAM TERHADAP ADAT PENARIKAN HARTA PEMBERIAN DALAM TUNANGAN YANG BATAL (STUDI KASUS DI DESA KANDANG KECAMATAN TEBO TENGAH KABUPATEN TEBO PROVISI JAMBI) - Adam Idris; Mawardi Mawardi (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2023)
Marriage always raises various problems. So is engagement, which is the first step toward marriage. Even though no contract can unite the two parties in a legal bond according to religious law, the cancellation of an engagement remains a serious problem that should be considered by Islamic family law practitioners and local religious leaders because the cancellation of an engagement can have legal consequences for both of them, related to the rights and status of the property given during the engagement process. Therefore, it is necessary to have an Islamic legal view to clarify the position of gifted assets in an aborted engagement by producing a conclusion that the gifted property is called a gift. From the description of the problem above, the author focused on three things; (1) how the practice of giving property in the engagement process was, (2) how the custom of withdrawing property gifted in a canceled engagement was, and (3) what the view of Islamic law regarding the custom of withdrawing gifted property in an annulled engagement (Case study in the village of Kandang Central Tebo District, Tebo Regency, Jambi Province) was. This type of this research was qualitative, through observation techniques, interviews, data collection, and documentation. The collected data were analyzed using triangulation research. The study results concluded that in its practice, the custom of withdrawing property from a canceled engagement in the village of Kandang must have invited the Traditional Leader, Village Officials, and also Nenek Mamak. According to the view of Islamic law, the gift of wealth in a engagement is a gift, it is a contract to give one person's property to another without any reward as a tribute or achievement, not a dowry, a grant, or charity. Because in Islamic law, gifts in engagement can be achieved through the istishlahiy/maqashidiy method, it is an ijtihad method that refers to maqasid al-shari'ah.